Thermal Energy Recovery from a Grid Connected Photovoltaic-Thermal (PVT) System Using Water as Working Fluid - Salami Tijani, Alhassan; Farhan Bin Md Tahir, Amer; Kubenthiran, Jeeventh; Singh Bhathal Singh, Baljit (International Journal of Engineering and Technology, 2018)
A Photovoltaic Thermal collector (PVT) is a combination of Photovoltaic (PV) and Thermal (T) collector. Many studies have tried to improve the electrical efficiency and thermal efficiency of this PVT system. The efficiency is influenced by many system design parameters and operating conditions such as the absorber temperature, velocity and pressure distributions. In this study, two new design concepts of absorber configuration of thermal collector have been investigated. This study also provides an important opportunity to advance the understanding of the effect of different geometrical configuration on the performance of the absorber.  Simulations were performed using ANSYS FLUENT 16.0 for both absorbers to determine the best absorber design that gives the highest thermal efficiency. Based on the simulations performed, perpendicular serpentine absorber proved to be the best design with the higher thermal efficiency of 56.45%.